Test of Gross Motor Development-3: Item Difficulty and Item Differential Functioning by Gender and Age with Rasch Analysis - Valentini, Nadia Cristina; Duarte, Marcelo Gonçalves; Zanella, Larissa Wagner; Nobre, Glauber Carvalho (International journal of environmental research and public health, 2022)
The assessment of motor proficiency is essential across childhood to identify children’s strengths and difficulties and to provide adequate instruction and opportunities; assessment is a powerful tool to promote children’s development. This study aimed to investigate the hierarchal order of the Test of Gross Motor Development-Third Edition (TGMD-3) items regarding difficulty levels and the differential item functioning across gender and age group (3 to 5, 6 to 8, and 9 to 10 years old). Participants are 989 children (3 to 10.9 years; girls n = 491) who were assessed using TGMD-3. For locomotor skills, appropriate results reliability (alpha = 1.0), infit (M = 0.99; SD = 0.17), outfit (M = 1.18; SD = 0.64), and point-biserial correlations (rpb values from 0.14 to 0.58) were found; the trend was similar for ball skills: reliability (alpha = 1.0), infit (M = 0.99; SD = 0.13), outfit (M = 1.08; SD = 0.52); point-biserial correlations (rpb values from 0.06 to 0.59) were obtained. Two motor criteria: gallop, item-1, and one-hand forehand strike, item-4, were the most difficult items; in contrast, run, item-2, and two-hand catch, item-2, were the easiest items. Differential item functioning for age was observed in nine locomotor and ten ball skills items. These items were easier for older children compared to younger ones. The TGMD-3 has items with different difficulty levels capable of differential functioning across age groups.